Tibetan Women’s Identification with the Sense of Community for the Chinese Nation: A Case Study of Wind - Chen, Xiaoyu; Shi, Chuan (Asia Pacific Economic and Management Review, 2025)
This article investigates Tibetan women’s identification with the consciousness of the Chinese national community through the characterization of Samdan and Gelak in Alai’s novel Wind. Samdan, marginalized by bodily stigmatization and social exclusion, reconstructs her subjectivity and achieves emotional integration into the community through maternal experience and the revaluation of life. Gelak positioned between traditional ethics and modern lifestyles, embodies an active form of identification with the national community through her resilience and sense of responsibility. Their lived experiences reveal the complex intersections of gender, ethnicity, and social structures, while also illustrating how minority women contribute to strengthening national belonging through everyday practices. By analyzing these female figures, this study deepens the understanding of minority women’s experiences and offers literary insights into the cultivation of a shared the sense of community for the Chinese nation.